Task‐based design of a synthetic‐collimator SPECT system used for small animal imaging. Issue 7 (1st June 2018) - Lin, Alexander; Kupinski, Matthew A.; Peterson, Todd E.; Shokouhi, Sepideh; Johnson, Lindsay C.
Abstract : Purpose: In traditional multipinhole SPECT systems, image multiplexing — the overlapping of pinhole projection images — may occur on the detector, which can inhibit quality image reconstructions due to photon‐origin uncertainty. One proposed system to mitigate the effects of multiplexing is the synthetic‐collimator SPECT system. In this system, two detectors, a silicon detector and a germanium detector, are placed at different distances behind the multipinhole aperture, allowing for image detection to occur at different magnifications and photon energies, resulting in higher overall sensitivity while maintaining high resolution. The unwanted effects of multiplexing are reduced by utilizing the additional data collected from the front silicon detector. However, determining optimal system configurations for a given imaging task requires efficient parsing of the complex parameter space, to understand how pinhole spacings and the two detector distances influence system performance. Methods: In our simulation studies, we use the ensemble mean‐squared error of the Wiener estimator (EMSEW ) as the figure of merit to determine optimum system parameters for the task of estimating the uptake of an 123 I‐labeled radiotracer in three different regions of a computer‐generated mouse brain phantom. The segmented phantom map is constructed by using data from the MRM NeAt database and allows for the reduction in dimensionality of the system matrix which improves the computational efficiency of scanning the system's parameter space. To contextualize our results, the Wiener estimator is also compared against a region of interest estimator using maximum‐likelihood reconstructed data. Results: Our results show that the synthetic‐collimator SPECT system outperforms traditional multipinhole SPECT systems in this estimation task. We also find that image multiplexing plays an important role in the system design of the synthetic‐collimator SPECT system, with optimal germanium detector distances occurring at maxima in the derivative of the percent multiplexing function. Furthermore, we report that improved task performance can be achieved by using an adaptive system design in which the germanium detector distance may vary with projection angle. Finally, in our comparative study, we find that the Wiener estimator outperforms the conventional region of interest estimator. Conclusions: Our work demonstrates how this optimization method has the potential to quickly and efficiently explore vast parameter spaces, providing insight into the behavior of competing factors, which are otherwise very difficult to calculate and study using other existing means.